Exploring Rehabilitation Professionals' Attitudes Toward Telerehabilitation Using Developing a New Questionnaire: A Cross ‐Sectional Study - Seyede Zohre; Elham Tavanai; Fatemeh Salmani; Mahdieh Karimi; Vida Rahimi (Health Science Reports, 2026)
ABSTRACT Background Telerehabilitation (TR) facilitates remote access to rehabilitation services, with its growth driven by advances in internet and communication technologies. However, its implementation may be influenced by professionals' attitudes. This study aimed to develop and validate a questionnaire to assess rehabilitation professionals' attitudes toward TR and to examine the association of demographic and professional characteristics with these attitudes. Methods This two‐phase cross‐sectional study involved 139 rehabilitation professionals from audiology, speech therapy, occupational therapy, and physiotherapy. In Phase 1, questionnaire development included face and content validity assessment by an expert panel. Exploratory factor analysis (EFA) identified the underlying structure, and confirmatory factor analysis (CFA) provided preliminary support for the model. Reliability was assessed using Cronbach's alpha. In Phase 2, the validated questionnaire was administered, and data were analyzed using independent t‐tests and one‐way ANOVA. Results The 33‐item questionnaire demonstrated excellent validity (CVI > 0.90) and reliability (Cronbach's α = 0.91). EFA identified a three‐factor structure explaining 76.17% of the total variance. Participants reported generally positive attitudes toward TR, particularly regarding its potential to expand access to services across wider geographical areas and support service delivery during pandemics. Consultation was perceived as the rehabilitation process most amenable to TR. Key perceived barriers included limited access to internet and communication technologies, concerns about service quality, and service undervaluation. Attitudes did not differ significantly according to age, educational level, work experience, or clinical field. Level of knowledge significantly affected one attitude domain ( p < 0.01), with a non‐linear pattern observed across knowledge levels. Conclusion The developed questionnaire demonstrated satisfactory psychometric properties for assessing rehabilitation professionals' attitudes toward TR. Rehabilitation professionals generally recognized the benefits of TR, particularly its potential to improve service accessibility and continuity of care, while also identifying important barriers related to infrastructure and service quality. The questionnaire provides a comprehensive tool for evaluating attitudes toward TR and may support future research on factors influencing its adoption across rehabilitation settings.